Studi Teologis Kata “Melepaskan” dalam Lukas 14:33 - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati; Andreas Fernando (STT Bala Keselamatan Palu, 2021)
Abstract: Many people today, even the majority of the world's population claim to be Christians. Whereas a real Christian has conditions and a price to be paid in order to become a true Christian, one of which is what Jesus said in Luke 14:33. The method in this research is to use the literature study method. The results of this study have several implications for Christians who claim to be true disciples of Jesus Christ, namely: First, Willingness to change the focus of life. Second, the willingness to live to leave the world. Third, the willingness to live apart from the power of mammon. Fourth, the willingness to live in holiness. Fifth, the willingness to renew the mind. Sixth, the willingness to live becomes a prop of Christ. Abstrak: Banyak orang saat ini, bahkan mayoritas penduduk dunia menyatakan diri sebagai Kristen. Padahal Kristen yang sebenarnya ada syarat dan harga yang harus dibayar agar menjadi seorang Kristen sejati, salah satunya adalah apa yang dikatakan oleh Yesus dalam Lukas 14:33. Metode dalam penelitian ini adalah menggunakan metode studi pustaka. Hasil dari penelitian ini ada beberapa implikasi yang harus hidupi orang Kristen yang mengaku murid sejati Yesus Kristus, yaitu: Pertama, Kesediaan merubah fokus hidup. Kedua, Kesediaan hidup meninggalkan dunia. Ketiga, Kesediaan hidup lepas dari kuasa mamon. Keempat, Kesediaan hidup dalam kesucian. Kelima, Kesediaan melakukan pembaharuan pikiran. Keenam, Kesediaan hidup menjadi alat peraga Kristus.